FORM AND CONTENT OF QUALIFICATION OPERATIONS BASED ON PROFESSIONAL COMPETENCE (European Journal of Interdisciplinary Research and Development, 2022)
The level of competence of each person, in particular, depends on what competence the specialist has. Qualification practice is a process of formation of competence of the student-practitioner, in which the personality of the practitioner is manifested as knowledge, methods and pedagogical skills and techniques that can be used (acquired) in his pedagogical activity. The main role in the professional development of a teacher is played by intellectual competence, the formation of which, without exception, covers all areas of education.